2022
DOI: 10.3889/oamjms.2022.7962
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Total Mesorectal Excision for Malignant Rectal Lesion: A Prospective Cohort Study

Abstract: AIMS: The main outcome of this study was to use the transanal total mesorectal excision (TaTME) technique for rectal cancer resection and to assess as a primary endpoint the short-term oncological outcome; in terms of circumferential resection margin, longitudinal resection margins (proximally and distally), and lymph nodes (LN) retrieval, while secondary endpoints were operative time, estimated blood loss, length of hospital stay, cost per case, and overall complication rate. METHODS: This was a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Four studies reported costs of one technique [25,28,31,32]. These studies included a total of 59 L-TME, 104 R-TME, 40 TaTME patients.…”
Section: Results Of Studies Assessing One Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported costs of one technique [25,28,31,32]. These studies included a total of 59 L-TME, 104 R-TME, 40 TaTME patients.…”
Section: Results Of Studies Assessing One Techniquementioning
confidence: 99%
“…This study reported total costs of $11,166.91. One study (Elbarmelgi et al) [32] reported costs of TaTME. This study reported total costs of $2,788.90.…”
Section: Results Of Studies Assessing One Techniquementioning
confidence: 99%
See 2 more Smart Citations